The Harmony of Space and Culture Environmental Policy: Accommodate The Rights of Indigenous Communities in Central Kalimantan Case - Rollys Suriani (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Environmental policies in Central Kalimantan often clash with the rights of indigenous communities, especially the Dayak, who have a resource management system based on local wisdom, while the expansion of plantation, mining, and infrastructure industries threatens their ecological sustainability and cultural existence. Therefore, more inclusive regulations are needed to protect the rights of indigenous communities and their ecosystems. The aim of this research is to analyze how environmental policies in Central Kalimantan accommodate the rights of indigenous communities in land and natural resource management and to understand the interaction between these policies and indigenous rights. This research uses a normative-empirical legal method with regulatory, conceptual, and sociological approaches to analyze regulations, the concept of indigenous rights, and the impact of environmental policies in Central Kalimantan, through literature study and interviews, which are then analyzed qualitatively. The research results show that environmental policies in Central Kalimantan still face challenges in accommodating the rights of indigenous communities, primarily due to slow regulatory implementation and frequent conflicts with industrial interests and infrastructure projects. Although there are environmental protection efforts such as plantation permit moratoriums and peatland ecosystem protection, their implementation often does not actively involve indigenous communities, resulting in ongoing land conflicts due to concessions granted without adequate consultation. The imbalance of interests in land management is also seen in the dominance of conservation policies and natural resource exploitation over the recognition of indigenous rights, exacerbated by weak legal recognition of customary land rights and the slow implementation of the Constitutional Court Decision No. 35/PUU-X/2012